2021
DOI: 10.1038/s41598-021-95880-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental enrichment and group size on the water use and waste in grower-finisher pigs

Abstract: The grower-finisher stage accounts for 64% of the total on-farm herd water use. Part of this is consumed by the pigs, but a part is also wasted. Drinking water usage and wastage is affected by different factors. We investigated how different group sizes and different levels of enrichment affect water usage (ingested plus wasted), water wastage, behavior and performance in grower-finisher pigs. Pigs (n = 672), 11 weeks of age (77 ± 2 days) were used for the experiment. The effect of group size: SMALL (12 pigs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This pattern in water use is similar to what was found by previous studies (16,20) with small differences in the timing of the peaks. Jensen et al (8) and Misra et al (6) only saw one large peak, but within the same hours as the two peaks found in the current study. Villagrá et al (21) found two peaks in the diurnal drinking pattern of pigs with different timing both compared to the current study and when comparing the two farms included in their study.…”
Section: Age Trend and Diurnal Patternsupporting
confidence: 84%
See 3 more Smart Citations
“…This pattern in water use is similar to what was found by previous studies (16,20) with small differences in the timing of the peaks. Jensen et al (8) and Misra et al (6) only saw one large peak, but within the same hours as the two peaks found in the current study. Villagrá et al (21) found two peaks in the diurnal drinking pattern of pigs with different timing both compared to the current study and when comparing the two farms included in their study.…”
Section: Age Trend and Diurnal Patternsupporting
confidence: 84%
“…Thus, the water use of pigs does not necessarily reflect the duration or frequency of pigs' drinking behavior. Misra et al (6) found an average water use across the finisher period of 10-11 L per pig and day. However, in their study pigs had access to water both from a drinking bowl and a nipple above the feed trough, making it possible for the pigs to mix the water with the feed.…”
Section: Age Trend and Diurnal Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…Most likely, it is a combination of both. However, Misra et al ( 106 ) showed lower levels of aggression in large stable groups compared to small stable groups of finisher pigs. Therefore, it is possible that levels of aggression are also lower in large compared to small groups of pregnant sows provided the groups are stable.…”
Section: Risk Factors For Chronic Stress In Pregnant Sowsmentioning
confidence: 97%